Transcriptions of ACO and ACS genes are involved in nitrate-dependent root growth of maize seedlings - Yao, Guoqi; Yan, Zhenwei; Ma, Shijun; Liu, Xia; Shan, Juan; Cao, Bing; Chen, Xiaole; Leng, Bingying; Mu, Chunhua (Frontiers in Plant Science, 2025)
Improving nitrogen use efficiency (NUE) is one of the major objectives for crop breeding. As nitrate signaling plays pivotal roles in nitrogen use of plants, factors in this pathway might be valuable for improving the NUE of maize. In this research, we performed Gene Set Enrichment Analysis (GSEA) of maize transcriptomes in response to nitrate and found that the ethylene action pathway might participate in nitrate signaling. Through a modified reciprocal best hit approach, we obtained 16 maize aminocyclopropane-1-carboxylic acid (ACC) oxidase (ACO) and four ACC synthase (ACS) homologs in maize genome. In silico analyses and the reverse transcription quantitative PCR assays demonstrated that ZmACCO7, ZmACCO5, ZmACCO15, ZmACCO35, and ZmACCO31 are the top five highly expressed ACO genes, and ZmACS1 is the most highly expressed ACS gene in the primary and seminal roots of maize. We discovered that ACO and ACS genes have different regulatory modes in response to nitrate provision. Some ACO genes, which are mainly expressed in root regions far from the root tip like ZmACCO7, are repressed by nitrate, while the others, which are mainly expressed in root regions near the root tip like ZmACCO5, are induced by nitrate. ZmACS1, which has more uniform expression across maize roots, is induced in root regions near the root tip and repressed in regions far from the root tip. A phenotypic analysis indicated that upregulation of ACO and ACS genes by nitrate is linked to repression of axial root elongation by nitrate while the downregulation of these genes is associated with the promotion of growth of lateral roots of the axial roots. In addition, differences in regulation of ACO and ACS genes by nitrate were observed between genotypes, which is related to the differences in the responses of their primary root growth to nitrate. These results suggested that the ethylene synthesis pathway is involved in the responses of maize roots to nitrate, which is associated with the remodeling of maize root architecture by nitrate.